2012
DOI: 10.1007/s00520-012-1590-9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis, cancer and renal insufficiency: low molecular weight heparin at the crossroads

Abstract: VTE is the second most common cause of death in cancer patients. Renal insufficiency is present in 50-60 % of cancer patients. Data from renal patients suggest that tinzaparin may be safe and effective for VTE treatment and prevention in cancer patients with renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…48 Cancer and Other Indications VTE is a common cause of morbidity and mortality in patients with cancer, with an estimated incidence between 4 and 20%. 49 Patients at greatest VTE risk are those who are hospitalized, undergoing active chemotherapy, or have metastatic disease. 50 Additional risk factors for VTE include treatment with certain chemotherapy regimens, the presence of certain tumors, and insertion of indwelling central venous catheters.…”
Section: Renal Failurementioning
confidence: 99%
See 1 more Smart Citation
“…48 Cancer and Other Indications VTE is a common cause of morbidity and mortality in patients with cancer, with an estimated incidence between 4 and 20%. 49 Patients at greatest VTE risk are those who are hospitalized, undergoing active chemotherapy, or have metastatic disease. 50 Additional risk factors for VTE include treatment with certain chemotherapy regimens, the presence of certain tumors, and insertion of indwelling central venous catheters.…”
Section: Renal Failurementioning
confidence: 99%
“…50 Additional risk factors for VTE include treatment with certain chemotherapy regimens, the presence of certain tumors, and insertion of indwelling central venous catheters. 49 The CLOT study compared warfarin and dalteparin for prevention of symptomatic, recurrent VTE in patients with active cancer and found that dalteparin was the more effective treatment, with recurrence in 8.0 versus 15.8% of patients. 51 Current guidelines recommend treating patients with advanced or metastatic cancer with LMWH monotherapy for the first 6 months after VTE.…”
Section: Renal Failurementioning
confidence: 99%
“…Venous thromboembolism (VTE), and pulmonary embolism (PE) in particular, are increasingly frequent complications in patients with malignancy, representing the second most common cause of death, following cancer itself 2,3. Despite this fact, the reported frequency of VTE in cancer patients is probably underestimated, given that autopsy rates of VTE can be as high as 50% compared with clinical rates of 4%–20% 4…”
Section: Cancer and Thrombosismentioning
confidence: 99%
“…This is not a minor feature; indeed, abnormal renal function is a common condition in patients with malignancy 37. According to the Renal Insufficiency and Anticancer Medications study group,3 50%–60% of patients with solid tumors, including the most common cancers including lung, breast, and prostate cancer, have abnormal renal function or renal insufficiency – a fact that may prove crucial when choosing the most appropriate LMHW for an individual patient 3…”
Section: Treatment Of Thrombosis In Cancer Patientsmentioning
confidence: 99%
“…Enoxaparin is a low-molecular-weight heparin, belonging to the category of organic acid compounds known as mucopolysaccharides, affecting thrombosis and angiogenesis in various cancers. Enoxaparin has an inhibitory effect on venous thrombosis, pulmonary embolism, acute coronary syndrome, thrombosis and angiogenesis in various cancers [1,2]. Angiogenesis in cancer is the process of new blood vessel formation around the tumor as endothelial cells multiply.…”
Section: Introductionmentioning
confidence: 99%